(untitled) (Agora for Physical Education and Sport, 2022)
What is a physically educated body? What kind of people did the francoism school produced that claimed to intervene methodically on the bodies of the new generations with the aim of improving their performance? How did the Youth Front use the body of the child and the youth, through Physical Education, with the purpose of forming a pool of educated citizens who would give permanence and stability to the state? How did the motto mens sana in corpore sano become the indoctrinating base of the Youth Front? These are some of the questions that this article will try to answer with the objective of looking at the Youth Front from another perspective. For this, it will focus on the male Physical Education of the Youth Front between the years 1940-1960, a period in which it became the National Youth Delegation. In this context, it will pay special attention to Physical Education in Primary Education, and to the educational gymnastics of the organization itself.